If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2m + -5) + -1m = 11 Reorder the terms: 2(-5 + 2m) + -1m = 11 (-5 * 2 + 2m * 2) + -1m = 11 (-10 + 4m) + -1m = 11 Combine like terms: 4m + -1m = 3m -10 + 3m = 11 Solving -10 + 3m = 11 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 3m = 11 + 10 Combine like terms: -10 + 10 = 0 0 + 3m = 11 + 10 3m = 11 + 10 Combine like terms: 11 + 10 = 21 3m = 21 Divide each side by '3'. m = 7 Simplifying m = 7
| (4z-3)-(8-z)=0 | | 3(2m)=1 | | 41+2k=3k+33 | | 237=4(7n+4)-3 | | 10x-15=6x-18 | | (-3)=4 | | 1/9(x-13)=5/9 | | (-6)=0 | | 8x-3x+2=x-2+4 | | -4e=-28 | | 6w-15=2(3w-5)-5 | | -6(6x+8)=168 | | h(t)=-10t^2+50t | | 6xy=z | | 725=475+25h | | 5(r-6)=23r | | 9x-3(7+2x)=-12 | | (2+7)+5= | | 9x+7=3x+17 | | -7x-12x+81=x+2x-27 | | 1.2w+1.97=0.43 | | 4(-10-5x)=-280 | | 3x+2x+3=45 | | 15y=3y+6y-2 | | 4(2d+4)=48 | | 7y=25 | | (3y)=3 | | 5m=7m-36 | | 5j-3j=4j-24 | | X+9=-3X-7 | | (y^2-7)(9y^2-2y+6)= | | x+270-3x=210 |